# Yahoo Web Search

1. Sort by

1. ### Suppose a/b = s/t where a,b,s,t are natural numbers and gcd(a,b)=gcd(s,t)=2. Prove a = s and s = t.?

I think you might mean that b=t (not s=t) In that case, let a = 2...only time s could equal t is if s=t=a=b=2, leading to 2/2 = 2/2... with the supplied info [i.e., you never used gcd(a,b...

2 Answers · Science & Mathematics · 19/02/2007

...a common factor. Factoring it out gives (c - d)(t + s) OR (t + s)(c - d) Answer: b

17 Answers · Science & Mathematics · 25/02/2009

3. ### Find s & t such that C-sA-tB is perpendicular to BOTH A and B?

Let D = (C - s · A - t · B) = (2-s-2t)i + (-1-s+t)j + (4-s-t)k If two vectors are perpendicular...

1 Answers · Science & Mathematics · 02/02/2008

4. ### How do I change this to y=ax(x-s)+t form?

I'm assuming that's the vertex form... First you have the vertex formula(-b/2a) Plug the -6 to the b and divide by 2(1)<---you don't have a number in front of the x so it...

6 Answers · Science & Mathematics · 06/09/2013

5. ### In how many ways can the letters P R O B A B I L I T I E S be arranged?

a) 13! / (2! * 3!) = 79,833,600

2 Answers · Science & Mathematics · 20/05/2008

6. ### If S varies inversely as the square of T, what happens to S if T is cut in half?

...that if you *fix* particular values of S and T, and maybe I will write them in lowercase ... thinking: in general, if S and T are related in some ...

1 Answers · Science & Mathematics · 18/04/2011

7. ### In linear algebra, show that if B is a square matrix, then BB^T and B + B^T is symmetric.?

... (XY)^T = Y^T X^T 1. (B B^T)^T = (B^T)^T B^T = B B^T...

2 Answers · Science & Mathematics · 28/05/2012

8. ### What's the proof for cos (a - b) = cos a * cos b + sin a * sin b ??

...: e^(ia - ib) = e^(ia) * e^(-ib) = [cos(a) + i sin(a)] * [cos(-b) + i sin(-b)] (Euler's Formula) = [cos(a) + i sin(a)] * [cos(b) - i sin(b)] = cos(a)cos(b) - i*cos...

4 Answers · Science & Mathematics · 10/02/2010

9. ### Finding the derivative of the integral?

If F(t) = integral from a(t) to b(t) of f(s) ds then F'(t) = da(t)/dt * f(a(t)) - d(b(t))/dt* f(b(t...

2 Answers · Science & Mathematics · 21/01/2016

10. ### Prove that a and b are integers, s and t are positive integers, and gcd(s,t)=1, then there exists some integer?

...bsx. Then, reducing mod s yields n = a * 1 + 0 = a (mod s) and reducing mod t yields n = 0 + b * 1 = b (mod t). I hope this helps!

1 Answers · Science & Mathematics · 16/09/2010